Light‐Induced Redox Looping of a Rhodium/CexWO3 Photocatalyst for Highly Active and Robust Dry Reforming of Methane. (23rd March 2022) - Yang, Yuying; Chai, Zhigang; Qin, Xuetao; Zhang, Zhenzhen; Muhetaer, Aidaer; Wang, Cong; Huang, Hanlin; Yang, Chaoran; Ma, Ding; Li, Qi; Xu, Dongsheng
Abstract: Dry reforming of methane (DRM) has provided an effective avenue to convert two greenhouse gases, CH4 and CO2, into syngas. Here, we design a DRM photocatalyst Rh/Ce x WO3 that invokes both photothermal and photoelectric processes, which overcomes the thermodynamic limitation of DRM under conventional conditions. In contrast to plasmonic or UV‐response photocatalysts, our photocatalyst produces a superior light‐to‐chemical energy efficiency (LTCEE) of 4.65 % with a moderate light intensity. We propose that a light‐induced metal‐to‐metal charge transfer plays a crucial role in the DRM reaction, which induces a redox looping between Ce to W species to lower the activation energy. Quantum mechanical studies reveal that a high oxygen mobility of Ce x WO3, accompanied with the formation of oxo‐bridge species, results in a substantial elimination of deposited C species during the reaction. Our catalyst design strategy could offer a promising energy‐efficient industrial process for DRM. Abstract : A photocatalyst for dry reforming of methane, Rh/Ce x WO3, invokes both photothermal and photoelectric activation processes. Light‐induced metal‐to‐metal charge transfer takes place in the photocatalyst, which induces a redox looping between Ce to W species. High oxygen mobility of Ce x WO3, accompanied with the formation of oxo‐bridge species, results in a substantial elimination of deposited C species during the reaction.